Analisis Personal Branding Studi Kasus Pada Akun Instagram @AALIYAH.MASSAID - Firmansyah, Ifan; Retnasary, Maya (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
Personal branding is the process of forming perceptions through one's personality, character and uniqueness to then be wrapped into an identity that has more strength compared to others by creating a positive image of its followers which is made into a marketing tool, Instagram is used as a place for self-branding, there is Instagram creating a new phenomenon among the public which is commonly referred to as Instagram celebrity or celebrity, celebrity is someone who has a fairly high popularity on Instagram, namely by having a large number of followers (followers) in large numbers of hundreds or even millions. This study uses the SMCR communication method, namely Source, Massage, Channel, Receiver. The approach used in this research is descriptive qualitative. The results of this study indicate that a celebrity needs to personalize their own branding in order to get a positive image of their followers and the personal branding that is built can be an opportunity to work with brands or products and the influence of personal branding is very important on the engagement of a celebrity.